2017
DOI: 10.5740/jaoacint.16-0337
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Tryptamines and β-Carbolines in Ayahuasca Beverage Consumed During Brazilian Religious Ceremonies

Abstract: Ayahuasca is a potent hallucinogenic beverage prepared from Banisteriopsis caapi in combination with other psychoactive plants. N,N-dimethyltryptamine, tryptamine, harmine, harmaline, harmalol, and tetrahydroharmine were quantified in ayahuasca samples using a simple and low-cost method based on SPE and LC with UV diode-array detection. The experimental variables that affect the SPE method, such as type of solid phase and nature of solvent, were optimized. The method showed good linearity (r > 0.9902) and repe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 8 publications
0
11
0
1
Order By: Relevance
“…In this context, the quantification of ayahuasca’s main alkaloids prior to its administration in animal or human studies is essential, as well as the knowledge of the tea’s sample origin, storage, and transportation conditions. Various analytical methods have been reported in the literature for the analysis of ayahuasca’s botanical preparations; these include solid-phase extraction (SPE), solid-phase microextraction (SPME), liquid–liquid extraction (LLE), and dilute-and-shoot for sample preparation prior to liquid chromatography or gas chromatography, both coupled to mass spectrometry and other detector types [ 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…In this context, the quantification of ayahuasca’s main alkaloids prior to its administration in animal or human studies is essential, as well as the knowledge of the tea’s sample origin, storage, and transportation conditions. Various analytical methods have been reported in the literature for the analysis of ayahuasca’s botanical preparations; these include solid-phase extraction (SPE), solid-phase microextraction (SPME), liquid–liquid extraction (LLE), and dilute-and-shoot for sample preparation prior to liquid chromatography or gas chromatography, both coupled to mass spectrometry and other detector types [ 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…18 The results demonstrated that menthone-thiosemicarbazone or coconut charcoal could be used as the extractant phase for determination of these alkaloids in ayahuasca beverages, since the concentrations were in agreement with those obtained using commercial silica as the adsorbent material (0.3 to 36.7 mg mL -1 ). 13 For these selected alkaloids, some studies have shown concentration range from 0.01 to 46.7 mg mL -1 . 6,9,19 The discrepancy in alkaloid concentration can be explained by the different methods of preparation as well as the amounts and proportions of the source plants.…”
Section: Methods Applicationmentioning
confidence: 99%
“…Ayahuasca samples were prepared from specimens of Banisteriopsis caapi stems and Psychotria viridis leaves by members of a religious group located in the city of Fortaleza, Ceará State, Brazil, according to the method reported by Santos et al 13 Aqueous decoctions of the plants were prepared from harvested material. At the end of the 20-h decoction, the extracts were bottled, frozen, and shipped to the Department of Chemistry at the Federal University of Sergipe.…”
Section: Sample Preparationmentioning
confidence: 99%
See 2 more Smart Citations